CHALLENGES OF DYNAMIC SIMULATION OF HIGH-SPEED ELECTROMAGNETIC VALVES OF GAS DISTRIBUTION DEVICES - E. I. Baida (National Technical University "Kharkiv Polytechnic Institute", 2020)
High-speed electromagnetic valves of gas distribution devices are used in modern missile and space technology as jet micro-motors of the executive elements of missile stabilization systems, as well as to control the movement of spacecrafts in space. The problem of creating such valves which are simple and reliable in the operation is relevant. In this work, it is proposed at the development and design stage to perform computer modelling of mutually coupled electromechanical processes, such as: distribution of transient electromagnetic field, transients in an electric circuit, and movement of an electromagnet armature. Besides, the calculation of the force with which the compressed gas acts on the corresponding structural elements of the valve is proposed to be performed by solving the system of Navier-Stokes equations. All problems are solved by numerical methods in axisymmetrical formulation with the corresponding initial and boundary conditions. Improvement of the accuracy of electromagnetic calculations and taking into account the movement of the armature of an electromagnet in the process of multiphysics numerical simulation is achieved using so-called tunable elastic meshes. The paper presents a comparative analysis of the numerical results obtained for several designs of electromagnets. The features of the dynamics of high-speed electromagnets of gas distribution valves during on and off operations are analyzed, the corresponding dynamic characteristics calculated using the proposed technique are presented.